Merkel Cell Carcinoma: Evaluation of the Clinico-Pathological Characteristics, Treatment Strategies and Prognostic Factors in a Monocentric Retrospective Series (n=143) - Rastrelli, Marco; Del Fiore, Paolo; Russo, Irene; Tartaglia, Jacopo; Dal Monico, Alessandro; Cappellesso, Rocco; Nicolè, Lorenzo; Piccin, Luisa; Fabozzi, Alessio; Biffoli, Bernardo; Di Prata, Claudia; Ferrazzi, Beatrice; et al. (Frontiers in Oncology, 2021)
Background: Merkel cell carcinoma (MCC) is a rare neuroendocrine tumor of the skin. The incidence of the disease has undergone a significant increase in recent years, which is caused by an increase in the average age of the population and in the use of immunosuppressive therapies. MCC is an aggressive pathology, which metastasizes early to the lymph nodes. These characteristics impose an accurate diagnostic analysis of the regional lymph node district with radiography, clinical examination and sentinel node biopsy. In recent years, there has been a breakthrough in the treatment of the advanced pathology thanks to the introduction of monoclonal antibodies acting on the PD-1 / PD-L1 axis. This study aimed to describe the clinico-pathological characteristics, treatment strategies and prognostic factors of MCC. Methods: A retrospective cohort study was conducted involving 143 consecutive patients who were diagnosed and /or treated for MCC. These patients were referred to the Veneto Institute of Oncology IOV-IRCCS and to the University Hospital of Padua (a third-level center) in the period between December 1991 and January 2020. In the majority of cases, diagnosis took place at the IOV. However, some patients were diagnosed elsewhere and subsequently referred to the IOV for a review of the diagnosis or to begin specific therapeutic regimens. Results: 143 patients, with an average age of 71 years, were affected mainly with autoimmune and neoplastic comorbidities. Our analysis has shown that age, autoimmune comorbidities and the use of therapy with immunomodulating drugs (which include corticosteroids, statins and beta-blockers) are associated with a negative prognosis. In this sense, male sex is also a negative prognostic factor. Conclusions: autoimmune and neoplastic comorbidities were frequent in the studied population. The use of drugs with immunomodulatory effects was also found to be a common feature of the population under examination. The use of this type of medication is considered a negative prognostic factor. The relevance of a multidisciplinary approach to the patient with MCC is confirmed, with the aim of assessing the risks and benefits related to the use of immunomodulating therapy in the individual patient.